Development of avian influenza virus H5 DNA vaccine and MDP-1 gene of Mycobacterium bovis as genetic adjuvant. - Jalilian, Babak; Omar, Abdul Rahman; Bejo, Mohd Hair; Mohamed Alitheen, Noorjahan Banu; Rasoli, Mehdi; Matsumoto, Sohkichi (BioMed Central, 2010)
Background Studies have shown that DNA vaccines can induce protective immunity, which demonstrated the high potential of DNA vaccines as an alternative to inactivated vaccines. Vaccines are frequently formulated with adjuvants to improve their release, delivery and presentation to the host immune system.